Developing 3D Automated Human Heart Model to Teach Abstract Concept of Biology (Universitas Negeri Semarang, 2021)
Models are direct replicas, images, or copies of real objects or figures. They are made in place of the original object and therefore used as such in place of the original. Inability to have access to mammalian internal organs is one of the challenges in teaching some concepts in Biology. Hence, the need to develop a 3-dimensional automated model of the human heart (3-DAMHH) to teach Biology concepts in Ilorin, Nigeria. The study was a developmental research design model. ADDIE model was adopted. The findings of this study revealed that a 3-dimensional (3D) automated model of the human heart was successfully developed with silicon gum, pop, oil paint, hosepipe, pumping devices, transformer, and diode. Findings also revealed that a 3-dimensional automated model of the human heart was cost-effective. This study recommends biology teachers use 3-DAMHH for teaching abstract concepts in biology. Abstrak Model adalah replika langsung, gambar atau salinan dari benda atau angka nyata yang dibuat sesuai dengan objek aslinya dan karenanya digunakan seperti objek aslinya. Ketidakmampuan untuk mengakses organ dalam mamalia merupakan salah satu tantangan dalam mengajarkan beberapa konsep dalam mata pelajaran Biologi. Oleh karena itu, perlu dikembangkan model jantung manusia otomatis 3 dimensi (3-DAMHH) untuk mengajarkan konsep Biologi. Dalam hal ini ini peneliti mengambil konteks di Ilorin, Nigeria. Penelitian ini merupakan penelitian pengembangan menggunakan model ADDIE. Temuan penelitian ini mengungkapkan bahwa: model jantung manusia otomasi 3 dimensi berhasil dikembangkan dengan permen karet silikon, pop, cat minyak, selang, perangkat pompa, transformator, dan dioda. Temuan lain juga mengungkapkan bahwa model otomatis 3 dimensi jantung manusia hemat biaya. Studi ini merekomendasikan agar para guru Biologi menggunakan 3-DAMHH untuk mengajar konsep abstrak dalam biologi dalam pembelajaran mereka.